Multidimensional ontology modelling - A robust methodology for managing complex and heterogeneous petroleum digital ecosystems - Nimmagadda, Shastri; Dreher, Heinz (IEEE, 2014)
Ontologies are described for elements, processes and chains of petroleum systems. Sedimentary basins, comprising of multiple petroleum systems are simulated in an integrated framework in which domain ontologies are integrated to generate a metadata. Several data views are generated from various data mining schemes. Domain knowledge is interpreted from these data views for decision support systems.